EVALUASI KINERJA GURU DAN IMPLIKASINYA TERHADAP PRESTASI BELAJAR PESERTA DIDIK DI MTS AL AMIRIYYAH DARUSSALAM - Wafi Bahrul Ilmi; Fajar Zainulloh; Nico Prasetyo; M Sidiq Purnomo (Universitas Islam Negeri Sumatera Utara Medan, 2025)
The main objective of this study is to analyse the implications of teacher performance evaluation for students' learning achievement at MTs Al-Amiriyyah Darussalam, with an emphasis on the relationship between teachers' pedagogical, professional, and managerial competences and their impact on students' motivation and learning outcomes. This research employs a qualitative approach with a case study design to understand the implications of teacher performance evaluation for students' academic achievement at MTs Al-Amiriyyah Darussalam. The research site and informants were selected purposively, involving teachers, the principal, and students. Data were collected through in-depth interviews, participatory observations, documentation of learning outcomes, and analysis of teacher performance evaluation documents. The data were analysed thematically with data triangulation to ensure credibility. This approach enables a holistic understanding of how teachers' pedagogical, professional, and managerial competences influence students' motivation, engagement, and academic achievement, while taking into account research ethics and data confidentiality.